2015
DOI: 10.1038/eye.2015.99
|View full text |Cite
|
Sign up to set email alerts
|

Cup-to-disc and arteriole-to-venule ratios in preterm birth

Abstract: Aims To investigate the influence of preterm birth on the optic disc and retinal vessels by measurements of cup-to-disc (C/D) ratio and arteriole-to-venule (A/V) ratio. Methods Eighty-three eyes of 42 preterm births were included. In the age-and sexmatched control group, 83 eyes of 42 full-term births were used. Fundus color photographs were taken. ImageJ software was used to calculate C/D and A/V ratios from the fundus images.Results Fundus photographs were taken at 8.01 ± 2.22 years of age for the preterm gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Only optic disk appearance looks unlike normal baby in our cases. We searched previous studies in PubMed using the keywords "preterm infant" and "cup disk ratio" or "large cupping disk" or "large cup disk" and found 14 papers published between 1978 and 2018 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Six papers reported that the C/D ratio is larger in premature infants than in full-term infants [4,5,7,9,10,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only optic disk appearance looks unlike normal baby in our cases. We searched previous studies in PubMed using the keywords "preterm infant" and "cup disk ratio" or "large cupping disk" or "large cup disk" and found 14 papers published between 1978 and 2018 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Six papers reported that the C/D ratio is larger in premature infants than in full-term infants [4,5,7,9,10,15].…”
Section: Discussionmentioning
confidence: 99%
“…We searched previous studies in PubMed using the keywords "preterm infant" and "cup disk ratio" or "large cupping disk" or "large cup disk" and found 14 papers published between 1978 and 2018 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Six papers reported that the C/D ratio is larger in premature infants than in full-term infants [4,5,7,9,10,15]. Three papers suggested that the C/D ratio is similar in preterm babies and full-term babies [3,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…The good survival rates among premature infants will result in increasing number of premature infants requiring further evaluation when an enlarged cup-disc-ratio was noted during Retinopathy of Prematurity (ROP) eye screening. Baseline values for infant Cup-Disc-Ratio (CDR) are available for premature infants but many were based on measurements taken when the children were older, except Park et al who reported on infants at 36 weeks [1][2][3][4][5][6]. The most convenient method for the examination of optic disc cupping is by clinical assessment as visualized by the binocular indirect ophthalmoscope [7].…”
Section: Introductionmentioning
confidence: 99%